EVOLUTION OF CLINICAL AND HORMONAL PARAMETERS IN PATIENTS WITH SOMATOTROPHIC PITUITARY ADENOMAS AFTER RADIOTHERAPY - Z.Yu. Khalimova; S.S. Issaeva; N.S. Zhuravleva; Sh.A. Abdumannopova (Central Asian Journal of Medicine, 2025)
Objective of the study. To evaluate the clinical and hormonal parameters in patients with somatotrophic pituitary adenomas in the early and long-term periods after radiotherapy. The analysis of the studies showed that hypopituitarism before radiotherapy (RT) was observed in 9.6% of patients with acromegaly. One year after RT, its frequency increased to 19.2% (p<0.05), after 2-5 years to 57.1% (p<0.001), and after 5-10 years to 68.1% (p<0.001). As seen, the degree of hypopituitarism positively correlates (r=0.57, Spearman) with the duration of the post-radiotherapy period, requiring the use of replacement hormone therapy. Our research suggests that different cells of the adenohypophysis have varying radiosensitivity. Thyrotrophs are highly sensitive, while corticotrophs are more resistant, which plays an important role in planning the management of patients with acromegaly and determining the outcomes of RT and long-term prognosis.